Traffic and traveller information (TTI). TTI messages via traffic message coding. Coding protocol for radio data system. Traffic message channel (RDS-TMC). RDS-TMC using ALERT Plus with ALERT C Part 4, (15th July 2000) - British Standards Institution,
No abstract available